Study of the Effect of Bulb Ratio and Blade Angle on Propeller Turbine Performance in Horizontal Flow using Numerical Simulation - Akhmad Nurdin; Dwi Aries Himawanto; Syamsul Hadi (TEKNIK, 2020)
This paper discusses numerical simulations of horizontal flow propeller turbines. Static bulbs located before the turbine can be used to increase water velocity and potentially increase the turbine's performance. The blade angle affects the gap between the blades, and this will also affect the performance of the turbine. Numerical simulations were conducted by using software Solid Works Flow Simulation 2016 and by using five blades in a static state. This study aimed to determine the effect of the bulb ratio and blade angle on the propeller turbine characteristics on horizontal flow. Bulb Ratio variations used in this study were 0, 0.4, 0.6, and 0.8, while the angle variations used were 20, 25, and 30 degrees. Each variation was tested at 0.02 m3/second. The results of this study indicated that the bulb ratio 0.6 with the 25-degree blade angle produces the highest torque